Medellín, from Theater of War to Security Laboratory - Jorge Giraldo-Ramírez; Andrés Preciado-Restrepo (Stability : International Journal of Security and Development, 2015)
No one city in the world has a greater experience in urban wars, demobilization and reintegration processes than Medellín. Over the past 30 years Medellín has suffered successive wars, sometimes simultaneously, involving drug cartels, urban militias, guerrillas and paramilitary forces. The city underwent military operations, peace negotiations and the return of thousands of fighters, all while facing ordinary violence. This article demonstrates that the central state interventions were crucial to producing needed changes to reduce violence, while efforts at the local level have been responsible for the changes in the local infrastructure and the sustainability of these improvements. Success depends on many vulnerable factors, though the main challenges to achieve the normalization of security in the city have been exposed.